Semi-active suspension control to improve ride and handling using magnetorheological (MR) damper. (1st January 2011) - Samin, Pakharuddin Mohd; Jamaluddin, Hishamuddin; Rahman, Roslan Abd; Abu Bakar, Saiful Anuar; Hudha, Khisbullah
This paper presents the simulation study of a semi-active suspension system using non-parametric model of magnetorheological (MR) damper. Hybrid stability augmentation-force control (HSAS-FC) is proposed as the control algorithm. The performance of the proposed control algorithm is analysed using validated full vehicle model and compared with modified hybrid skyhook groundhook control and passive system. The HSAS-FC is used to estimate the desired force needed to simultaneously improve ride dynamics and handling performance. The stability augmentation system (SAS) is to improve ride, meanwhile the force control (FC) is used to control roll rate and pitch rate due to lateral load transfer and longitudinal load transfer. An adaptive inverse current model was developed to produce the required current by the MR damper. The results show the new system is effective in isolating vehicle body from unwanted motions at the body centre of gravity. The amplitude and settling time of unwanted body motions are reduce for ride.